Pengaruh Jumlah Anak Terhadap Pendapatan Hasil Perkebunan Kemiri di Desa Maikang Kecamatan Alor Selatan Tahun 2020 Menggunakan Metode Chi Kuadrat - Leonardus Frengky Obe; Damaris Lalang; Vera Lakapeni; D. Fatin (Jurnal Ilmiah Wahana Pendidikan, 2021)
Given that most of the people of Maikang Village think that the more children in a family, the income from candlenut plantations will also increase, so this study aims to determine the Effect of the Number of Children on Candlenut Plantation Income in Maikang Village, Alor Selatan District in 2020. The Chi-Square method is a hypothesis test comparing the frequency of observations that occur or occur with the frequency of expectations or expectations. From the results of this study, it is known that the calculated Chi-squared = 8.1890 and the table Chi-squared with dk 1 and an error rate of 10% = 2.706. If you compare count (8.1890) with table (2.706), then 2 count is more than 2 table. This shows that there is an influence between the number of children on the income of candlenut plantations.